Surface modification of parylene-N with UV-treatment to enhance the protein immobilization - Ko, Hyuk; Choi, Yong-Hwan; Chang, Seo-Yoon; Lee, Ga-Yeon; Song, Hyun-Woo; Chang, Young Wook; Kang, Min-Jung; Pyun, Jae-Chul (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In this work, we demonstrate that parylene-N can improve the immobilization efficiency of proteins through a UV-treatment. The UV-treatment can be carried out under atmospheric conditions at room temperature without the need for the gas control and vacuum conditions that are required for plasma-treatment. Additionally, the UV-treatment does not require the collision of high-energy gas molecules; the surface roughness of parylene-N is maintained throughout the modification process. To characterize the physical and chemical properties of the UV-treated parylene-N, contact angle (advancing and receding), grazing angle FT-IR spectroscopy (for thin films), and X-ray photoelectron spectroscopy (for depth profiling) measurements were carried out. The protein immobilization efficiency of the UV-treated parylene-N was estimated with SPA biosensors using proteins with different surface charges, and the long-term stability of the protein immobilization capabilities were also estimated as compared with plasma-treated parylene-N. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: AUTODISPLAYED Z-DOMAINS; SPR BIOSENSOR; ELECTROCHEMICAL ELISA; ESCHERICHIA-COLI; PM-IRRAS; H FILM; IMMUNOASSAY; LAYER; ELECTRODE; ASSAY